Characteristics of Tuberculous Meningitis Patients at M.Djamil Padang Hospital in 2024 - Fanny Adhy Putri; Yuliarni Syafrita; Djong Hon Tjong; Dwitya Elvira; Nurvalinda Nurvalinda (Universitas Pahlawan Tuanku Tambusai, 2025)
Tuberculous meningitis (TBM) is the most severe form of extrapulmonary TB, causing high morbidity and mortality. The Global TB 2022 report estimates that there are at least 100,000 people with MTB each year. In 2021, there were at least 13,400 MTB cases in Indonesia, or about 8% of the global estimate. To determine the characteristics of tuberculous meningitis patients at M. Djamil Padang Hospital in 2024. A descriptive study with cross-sectional method. The sampling technique used was purposive sampling by collecting medical record data of TBM patients at Dr. M. Djamil Padang Hospital in 2024. The number of samples that met the inclusion and exclusion criteria was 45 sample. Data were analyzed using SPSS. Univariate analysis was used to assess the characteristics of patient and presented in the form of a frequency distribution table. The average age of TBM patients in this study was 31 years, dominated by male gender (55.6%). Most of the TBM patients had normal nutritional status (64.4%) and only 17.8% of patients were underweight. Only 13.3% of TBM patients had a history of TB and 6.7% of patients had positive HIV status. Around 4.76% and 11.1% of patients had comorbid DM and hypertension. Most patients were in stage II BMRC (71.1%). Hydrocephalus was the most common CT Scan finding, which was 46.7%. Only 26.7% of patients died during treatment. Tuberculous meningitis is more common in men, with stage II BMRC, has hydrocephalus, and more than a quarter of MTB patients died during treatment.